MetaVis: metadata visualization using JUNG's library - Nasharuddin, Nurul Amelina; Abdul Hamid, Jamaliah; Selamat, Mohd Hasan; Ibrahim, Hamidah; Abdullah, Rusli; Abdullah, Muhamad Taufik; Wan Isa, Wan Malini (Universiti Utara Malaysia, 2008)
In this paper we present a prototype for a new interface called MetaVis for search engines through graph drawing representation of interconnected metadata. This interface represents the metadata as connected nodes in a graph. The result will be displayed in a network with the keyword as the center and interrelated metadata as its connected nodes. Users will then be able to select any of the interrelated metadata nodes to navigate further all details connecting titles, sources, emails and addresses to the author. This fluidity of navigating related information from the interconnected nodes overcomes the rigidity of single layer search which is often time consuming. This interface which implemented Java Universal Network/Graph Framework (JUNG) has a few functions that enable users to manipulate the concepts graph.